PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN - Bagaskoro, Bagaskoro (AGUSPATI Research Institute, 2021)
A company in carrying out business activities or business activities, generally what the company must pay attention to is customer orientation, which concerns what the company must satisfy its customers. High company performance and service quality provided by a business and services are the most important factors for customer satisfaction. Companies must pay attention to things that are considered important by consumers and customers so that they are satisfied according to their expectations. This study aims to determine the effect of service quality and brand image on customer satisfaction at PT Adira Finance Cimanggis branch. The number of respondents is 100 customers of PT Adira Finance. The analysis technique uses multiple regression analysis. The results showed that, there was no significant effect between Service Quality on Customer Satisfaction, there was a significant positive effect between Brand Image on Customer Satisfaction. Taken together, there is an influence between Service Quality and Brand Image on Customer Satisfaction